Clinicopathological Correlation in Dysplastic and Malignant Lesions of The Oral Cavity and Oropharynx in Tertiary Care Center in Central India - Yadav, Priyanka; Malik, Reeni; Balani, Sharda; Nigam, Rajendra Kumar; Jain, Pramila; Tandon, Puneet (Annals of Pathology and Laboratory Medicine, 2019)
Background: Late detection and diagnosis of oral and oropharyngeal carcinomas are responsible for the related increased morbidity and mortality. Understanding the risk factors and patterns of malignancy can help early identification and prompt treatment of patients with oral cancers. In the current study, we aimed to study the pattern of oral dysplastic and neoplastic lesions in tertiary care centre in central India and study its association with various risk factors. Methods: The oral biopsy tissues received in the Department of Pathology, GMC, Bhopal for histopathological evaluation during the duration of one and a half years were included in the study. The data was analysed by appropriate statistical tests (software SPSS). Result: A total of 334 cases presented for oral neoplastic lesions during the study period with mean age of presentation of malignant lesions and premalignant lesions being 51 years and 46 years respectively. 78.3% cases were reported as malignant lesions with majority being Well Differentiated Squamous Cell carcinomas (57%) among oral cavity lesions and Moderately Differentiated Squamous Cell Carcinoma (41%) among oropharyngeal lesions. 87% of patients reported use of tobacco chewing smoking and alcohol, either alone or in combination. Conclusion: High risk individuals included males more than 35 years of age indulging in tobacco chewing, smoking and alcohol with exclusive tobacco chewing associated more with oral malignant lesions whereas the smoking and alcohol along with tobacco chewing associated more with oropharyngeal lesions. Substance abuse awareness programs and screening early lesions in high risk individuals are recommended to curtail oral malignancies.